PENINGKATAN PEMAHAMAN PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN PANTUN BERDENDANG PADA SISWA SMP NEGERI 1 SEGEDONG - Sinaga, Limjon Parasian; Mering, Aloysius; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is drived by the lacking of students character education value understanding on SMP Negeri 1 Segedong. This is proved as well by the achievement percentage of students attitude in attending the class which rated very low (SK) that is 19,44% or 7 out of 36 students. The purpose of this research was to increase the students character values. This research used a descriptive approach by the application of Classroom Action Research which is held in pre cycle and 3 cycle application of action. The sample chosen is a purposive sampling on the B class of 8th grade which has the character value understanding problem. The technique applied in data collecting is a direct observation and scoring technique, and the technique applied in data analysis is a descriptive qualitative analysis and descriptive qualitative analysis. According to the analysis result about the increasing of students character educational value by applying the study of pantun berdendang as a media is concluded that has increasing progress in the students understanding of achievement which could reach 100%. This result concludes that the applied study of pantun berdendang as a media of study in this research could increase the students character value understanding. Keywords: study of pantun berdendang, character education